PEMBELAJARAN KOSAKATA BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) LEVEL A-1 DENGAN MENGGUNAKAN PERMAINAN KARTU KATA DAN KARTU GAMBAR - Hirza Rahmayati (Balai Diklat Keagamaan Medan, 2022)
Indonesian for Foreign Speakers or BIPA is a branch of basic Indonesian linguistic teaching that focuses on foreigners as learners. These learners prepare themselves to learn Indonesian formally for educational or work needs. In this study, the students consisted of eight female and male students, Universitas Pendidikan Indonesia who came from South Korea. They are BIPA level A-1 learners or beginners with educational and work purposes. The focus of the material in this research is learning Indonesian vocabulary BIPA level A-1 by using word card games and picture cards. Vocabulary is fundamental in learning a new language. The higher one's vocabulary, the more communicative one's language skills will be. to maximize this learning process, word card game techniques and picture cards were used which were created by the teacher as well as the researcher. Data collection techniques used are tests, questionnaires, and interviews. The results of this study indicate that students are very enthusiastic and interested in learning vocabulary using word cards and picture card game techniques. Based on the results of the data obtained, it was found that there was a significant increase in test scores between the pretest and posttest. The test presented is a multiple-choice test with 10 questions with 5 alternative answers. Then, the mean of the questionnaire data shows a strong category with a score of 78.7. Questionnaires were distributed to students using a Likert Scale with 10 questions and 5 alternative categories of answers. This significant increase in posttest scores is relevant to the interviews that have been conducted. The students hope that this kind of learning technique will continue to be improved by BIPA teachers.